公猪精液溯源管理系统及方法 (2024)
本发明公开了公猪精液溯源管理系统及方法，属于数据分析领域，本发明获取需要核对的精液图像数据，同时获取取精时全部公猪的身体体质信息，将需要核对的精液图像数据和储存环境数据导入精液异常分析模型中分析精液起始异常指数，将取精时全部公猪的身体体质信息导入身体体质异常分析模型中分析体质异常指数，将精液起始异常指数和体质异常指数导入精液与体质匹配分析策略中进行精液与公猪体质匹配分析，根据精液与公猪体质匹配结果进行精液与公猪的信息对应分析，对精液情况和公猪体质进行准确匹配分析，对精液源头进行快速准确查找，提高了精液溯源的准确性和速度。 The invention discloses a boar semen traceability management system and a boar semen traceability management method, and belongs to the field of data analysis. Semen image data needing to be checked and storage environment data are imported into a semen abnormality analysis model to analyze a semen initial abnormality index, and body constitution information of all boars during semen collection is imported into a body constitution abnormality analysis model to analyze a constitution abnormality index. And importing the semen initial abnormality index and the constitution abnormality index into a semen and constitution matching analysis strategy to carry out semen and boar constitution matching analysis, carrying out semen and boar information corresp